Enhancement of natural and forced convection condensation using three-dimensional extended structures - Ho, Jin Yao (2019)
Condensation heat transfer is widely used in many engineering applications such as in air-conditioning systems, power generators and desalination plants. Due to its extensive applications, enhanced condensation heat transfer is essential for improving system efficiency and reducing energy consumption. The use of fin structures has the potential for condensation applications due to their increased heat transfer area. In addition, the fin geometry is also essential to promote condensate thinning by surface tension forces. However, existing extended surfaces are largely two-dimensional fins which have the disadvantage of large condensate retention. Three-dimensional pin fins, on the other hand, have the potential of reducing condensate retention. However, existing three-dimensional fin designs have poor geometrical variations. To overcome these issues, three-dimensional pin fins of new geometries which take advantage of surface tension effects and reduced condensate retention can be fabricated by selective laser melting (SLM). The objectives of this thesis are to investigate natural and forced convection condensation using three-dimensional pin fin structures of new geometries and fin parameters. The test specimens are fabricated by SLM as it provides the design freedom to produce structures with complex geometries and good dimensional accuracy. A condensation chamber is developed to study the natural convection condensation on fin arrays whereas forced convection condensation in enhanced tubes is investigated using a two-phase flow facility. Steam and R134a are used as the working fluids. For natural convection condensation, three-dimensional conical, sinusoidal and cylindrical pin fins of different fin heights and fin pitches are investigated and comparisons are made against the equivalent two-dimensional fins. Visualisation studies are also performed to determine the liquid retention height on the fin structures. The results show that three-dimensional pin fin structures exhibit better heat transfer performance than the equivalent two-dimensional fins. This is mainly due to the lower condensate retention height and the significant surface tension effects. In addition, the conical pin fin surfaces also show the highest heat transfer performance as compared to other three-dimensional pin fins. A theoretical model which accounts for the effects of surface tension and gravitational forces on the liquid film is developed to evaluate the condensation performance of a conical pin fin. The modelling results validated the existence of a thin liquid film region near the fin tip. In addition, due to the concave trough of the liquid pool, another thin liquid film region is produced near the fin base. The surface tension force also reduces the film thickness in the circumferential direction. These mechanisms have resulted in the significant heat transfer enhancements of the conical pin fin structure. For forced convection condensation, the condenser tubes with conical and domed-shape pin fins were fabricated by SLM. These condenser tubes show good integrity and are able to sustain high pressure operation. This is also the first time the SLM technique is used to produce enhanced tubes for improving forced convection condensation with high pressure refrigerant. The experiments are conducted using R134a as the working fluid and the effects of refrigerant mass flux, vapour quality, circumferential fin pitch and longitudinal fin pitch on the heat transfer coefficient and pressure drop are investigated. It is found that the heat transfer coefficients of the conical pin fin tubes increase with increasing vapour quality and mass flux and these values are also significantly higher than those of the plain tubes. Both circumferential and longitudinal fin pitch were found to significantly affect the heat transfer coefficient of the conical pin fin tubes whereas the pressure drop values are affected only by the change in the circumferential fin pitch. Based on the boundary layer approach, a semi-empirical model is developed to predict the Nusselt numbers of the conical pin fin tubes. Relatively reasonable predictions are achieved with an overall mean absolute error of 10.5%.